2020
DOI: 10.1007/s11614-020-00399-9
|View full text |Cite
|
Sign up to set email alerts
|

Individual social capital and subjective well-being in urban- and rural Austrian areas

Abstract: In this study we investigated the amount of social capital as well as its effect on subjective well-being for the whole Austrian population and separately for rural-and urban areas. By using the Austrian Social Survey 2018, we were able to analyze various social capital dimensions based on a conceptual model developed by Kawachi (2008), namely informal and formal social capital, social support as well as social and institutional trust. We observed differences between rural and urban areas in the social-capital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 42 publications
0
6
0
5
Order By: Relevance
“…Literature Review SK tiek izdalīts trīs veidos: piesaistošais (bonding), savienojošais (brinding) un sasaistošais (linking). Katrā no veidiem ietilpst divas dimensijas: kognitīvā (cognitive) un strukturālā (structural) (Šuriņa un Mārtinsone, 2020), un katra no dimensijām sastāv no vairākiem elementiem: sociālā uzticēšanās, ko var iedalīt vispārējā sociālā uzticēšanās, uzticēšanās tuviniekiem un institucionālā uzticēšanās; uztvertais sociālais atbalsts no tuviniekiem; uztvertais sociālais atbalsts no paziņām; sociālas attiecības un piederības izjūta (Beilmann et al, 2017;Ehsan et al, 2019;Belanger et al, 2020;Glatz & Bodi-Fernandez, 2020).…”
Section: Literatūras Apskatsunclassified
See 2 more Smart Citations
“…Literature Review SK tiek izdalīts trīs veidos: piesaistošais (bonding), savienojošais (brinding) un sasaistošais (linking). Katrā no veidiem ietilpst divas dimensijas: kognitīvā (cognitive) un strukturālā (structural) (Šuriņa un Mārtinsone, 2020), un katra no dimensijām sastāv no vairākiem elementiem: sociālā uzticēšanās, ko var iedalīt vispārējā sociālā uzticēšanās, uzticēšanās tuviniekiem un institucionālā uzticēšanās; uztvertais sociālais atbalsts no tuviniekiem; uztvertais sociālais atbalsts no paziņām; sociālas attiecības un piederības izjūta (Beilmann et al, 2017;Ehsan et al, 2019;Belanger et al, 2020;Glatz & Bodi-Fernandez, 2020).…”
Section: Literatūras Apskatsunclassified
“…Piesaistošais SK rodas no attiecībām homogēnu grupu ietvaros (ģimenes locekļi, tuvinieki) (Pitas & Ehmer, 2020). Tā kognitīvā dimensija ietver uztverto sociālo atbalstu (Glatz & Bodi-Fernandez, 2020) un uzticēšanos tuviniekiem (Beilmann et al, 2017), kā arī piederības izjūtu (Belanger et al, 2020). Savukārt piesaistošā SK strukturālā dimensija attiecas uz kontaktu biežumu ar tuvākajiem cilvēkiem jeb sociālām attiecībām (Ehsan et al, 2019).…”
Section: Literatūras Apskatsunclassified
See 1 more Smart Citation
“…Empirical evidence has also suggested that these prehistoric groups were broadly made up of biological and affinal relatives [ 10 ]—individuals who would have been protective of each other’s well-being in general due to it being an important determinant of the evolutionary success of their (future) biologically related descendants [ 12 ••]. This is in stark contrast to the relatively common evolutionarily recent phenomenon of solo-living, or living apart from and having relatively irregular interactions with most of one’s kin, especially among urban-dwelling individuals [ 8 , 9 , 13 ]. Thus, in light of the empirically suggested stress-alleviating role of kin support [ 14 , 15 ] and the knowledge that sleep difficulties can result from the pressures of life [ 16 ], it is believed that the comparative lack of easily accessible support from relatives, in addition to the issues surrounding solo-living itself, is likely a risk factor for developing insomnia symptoms among urban residents [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Визначенню місця соціального капіталу в забезпеченні ефективного функціонування різноманітних складних ієрархічних соціально-економічних систем приділяється особлива увага багатьох дослідників. Так, C. Glatz (2020) та О. Bodi-Fernandez (2020) визначають вплив кількості соціального капіталу на суб'єктивне благополуччя всього населення Австрії і окремо для сільських і міських районів [22]; L. Alcorta (2020), J. Smits (2020), H. J. Swedlund (2020) та de Jong E. (2020) розкривають важливість соціального капіталу в досягненні соціальних трансформацій та економічного розвитку на прикладі 27 країн Африки [16]. Вплив соціального капіталу та інтеграції знань на ефективність інновацій на прикладі віртуальних команд досліджують J. Li (2020), X. Wan (2020) і X. Wang (2020) [24], тоді як G.-Q.…”
unclassified